Are Structured Data Structured Identically? - Los, R. K.; Roukema, J.; van Ginneken, A. M.; de Wilde, M.; van der Lei, J. (Methods of Information in Medicine, 2005)
Objective: OpenSDE is an application that supports structured recording of narrative patient data to enable use of the data in both clinical practice and clinical research. Reliability and accuracy of collected data are essential for subsequent data use. In this study we analyze the uniformity of data entered with OpenSDE. Our objective is to obtain insight into the consensus and differences of recorded data.Methods: Three pediatricians transcribed 20 paper patient records using OpenSDE. The transcribed records were compared and all recorded findings were classified into one of six categories of difference.Results: Of all findings 22% were recorded identically; 17% of the findings were recorded differently (predominantly as free text); 61% was omitted, inferred, or in conflict with the paper record.Conclusion: The results of this study show that recording patient data using structured data entry does not necessarily lead to uniformly structured data.
Keywords: Structured data entry; information storage and retrieval; medical records